WORK TOGETHER AND BE GLOBAL LEADERS, URGES THE RAJA OF PERLIS TO USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 24 April 2015 The Raja of Perlis, who is also the Chancellor of Universiti Sains Malaysia (USM), H.R.H Tuanku Syed Sirajuddin Ibni AlMarhum Tuanku Syed Putra Jamalullail, urged the USM community to continue being fully committed in their work to achieve success in the future. His Royal Highness also hoped that those in the USM community would aspire to be global leaders in their own respective fields.